Claude Waller, Digest of the Ordinances of the City of Nashville, to Which are Prefixed the State Laws Incorporating, and Relating to, the City, with an Appendix Containing Various Grants and Franchises Page 346-347, Image 354-355, § 652 (1893) - (:unkn) unknown (General Publisher, 1893)
If any person or persons shall fire any gun or pistol, cast, throw or fire any squib, rocket, cracker, or other combustible fire-works within the limits of the corporation, every such person, for every such offense, shall forfeit and pay the sum of five dollars
--
Keywords: DISCHARGE